Process migration in unix - Amarillo, Alejandro B. (Animo Repository, 1996)
This thesis discusses how a process migration mechanism was designed and implemented on workstation clusters running UNIX FreeBSD version 2.1.0. The mechanism was built entirely outside the kernel, which resulted in a simple, transparent, and portable implementation. Processes which communicate via signals, access NFS files, and those that depend on their execution environment may be migrated without sacrificing functionality. Migration was achieved by saving the process context to checkpoint files, and using these files to restore the process on the destination host. Programs are linked with a migration library in order for them to be check pointed and eventually migrated.